Best Practices for Elderly Hip Fracture Patients: A Systematic Overview of the Evidence - Beaupre, Lauren A (Blackwell Science Inc, 2005)
OBJECTIVES: To determine evidence-based best practices for elderly hip fracture patients from the time of hospital admission to 6 months postfracture. DATA SOURCES: MEDLINE, Cochrane Library, CINAHL, Embase, PEDro, Ageline, NARIC, and CIRRIE databases were searched for potentially eligible articles published between 1985 and 2004. REVIEW METHODS: Two independent reviewers determined studies appropriate for inclusion using standardized selection criteria, extracted data, evaluated internal validity, and then rated studies according to levels of evidence. Only Level 1 or 2 evidence was included in our summary of clinical recommendations. RESULTS: Spinal anesthesia, pressure-relieving mattresses, perioperative antibiotics, and deep vein thromboses prophylaxes had consistent evidence of benefit. Routine preoperative traction was not associated with any benefits and should be abandoned. Types of surgical management, postoperative wound drainage, and even “multidisciplinary” care, lacked sufficient evidence to determine either benefit or harm. There was little evidence to either determine best subacute rehabilitation practices or to direct ongoing medical issues (e.g., nutrition). Studies conducted during the subacute recovery period were heterogeneous in terms of treatment settings, interventions, and outcomes studied and had no clear evidence for best treatment practices. CONCLUSIONS: The evidence for perioperative practices is relatively robust and evidence-based perioperative treatment guidelines can be easily established. Conversely, more evidence is required to better guide the care of elderly patients with hip fracture during the subacute recovery period and convalescence.